A Dramatic Rewriting of the Homeric Odyssey: Circe y los cerdos by Carlota O’Neill - Fernández Garrido, Regla (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2024)
This paper studies the play Circe y los cerdos by Carlota O’Neill, in which the author rewrites the episode of Circe and Odysseus from the Homeric Odyssey. It analyses how the main characters are portrayed (Circe, Odysseus and the pig-men) and the intertextual relations between the two texts, especially how the lines of the Homeric poem, often translated literally from Leconte de Lisle’s French version of 1893, are transposed into the dramatic text. The resources used by the author to actualise the Homeric episode and give it a new dimension, in line with her ideas and the message she wants to convey, are also pointed out.